MOTIVATION, ANXIETY, AND PLEASURE (FOREIGN LANGUAGE ENJOYMENT) IN LEARNING ENGLISH: INTERACTIONS AND PEDAGOGICAL IMPLICATIONS (Web of Humanities: Journal of Social Science and Humanitarian Research, 2026)
The article examines three key psychological factors influencing English language success: motivation, anxiety, and pleasure from learning a foreign language (Foreign Language Enjoyment, FLE). Modern approaches to studying the emotional-motivational sphere in English teaching methodology, including self-determination theory, the concept of foreign language anxiety, and positive psychology, are analyzed. Special attention is paid to how FLE can compensate for the negative impact of anxiety and enhance learners' motivation. In conclusion, pedagogical strategies for increasing motivation and FLE and reducing anxiety in English lessons are proposed.